2013
DOI: 10.1007/s00256-013-1796-z
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral insufficiency fracture of the femoral head in a patient with alkaptonuria

Abstract: We report a patient with alkaptonuria accompanied by bilateral rapidly destructive arthrosis of the hip. The destruction of the left hip joint with its severe functional impairment necessitated total hip arthroplasty (THA). The outcome was satisfactory. Both magnetic resonance imaging (MRI) and pathologic findings were compatible with a subchondral insufficiency fracture. A year and half later, during a follow-up visit, the patient complained of right coxalgia. Radiography showed that the right femoral head ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Several potential risk factors have been proposed in the literature, including: (I) ageing; (II) female gender; (III) underlying health problems such as rheumatoid arthritis, diabetes mellitus and systemic lupus erythematosus; (IV) lower bone mineral density; (V) higher BMI; (VI) medicinal drug use including NSAIDs and corticosteroid; (VII) alcoholism (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24)27,29). In this study, we evaluated the risk factors and found the only prevalent factors were: (I) age greater than 60 years; (II) female gender; (III) underlying systemic disease such as rheumatoid arthritis, diabetes mellitus or systemic lupus erythematosus (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)23,24). There is insufficient evidence to support the relationship between BMD, BMI, medication and alcoholism and the o...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several potential risk factors have been proposed in the literature, including: (I) ageing; (II) female gender; (III) underlying health problems such as rheumatoid arthritis, diabetes mellitus and systemic lupus erythematosus; (IV) lower bone mineral density; (V) higher BMI; (VI) medicinal drug use including NSAIDs and corticosteroid; (VII) alcoholism (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24)27,29). In this study, we evaluated the risk factors and found the only prevalent factors were: (I) age greater than 60 years; (II) female gender; (III) underlying systemic disease such as rheumatoid arthritis, diabetes mellitus or systemic lupus erythematosus (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)23,24). There is insufficient evidence to support the relationship between BMD, BMI, medication and alcoholism and the o...…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a unique presentation of severe bone destruction as a manifestation of chronic myeloid leukemia in the absence of blast crisis (33). There were bone marrow edema on acetabulum, femoral head and neck and the weight-bearing area and the articular cartilage was absent with the subchondral insufficiency fracture or subchondral bone destroyed (2,3,(5)(6)(7)(8)10,34,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular interest in our case was the lack of ochronotic pigment in a newly formed osteophyte, a finding we believe has not been previously reported. A recent paper by Yamada et al, however, does show gross lack of ochronotic staining in an osteophyte, although it is not noted [18]. The apparent forming osteophyte is in the formation phase of bone, with the synthesis of new organic matrix, not the catabolism of existing proteins.…”
Section: Discussionmentioning
confidence: 99%